2021
DOI: 10.1136/bmjebm-2020-111576
|View full text |Cite
|
Sign up to set email alerts
|

Short and long-term psychosocial consequences of participating in a colorectal cancer screening programme: a matched longitudinal study

Abstract: ObjectivesTo investigate the psychosocial consequences of receiving a false-positive (no abnormalities) result or being diagnosed with polyps compared with receiving a negative result in a colorectal cancer (CRC) screening programme.Design and settingThis was a longitudinal study nested in the roll-out of the Danish CRC screening programme that targets all individuals aged 50–74 years.ParticipantsIn the inclusion period (April–September 2017), all positive screenees (n=1854) were consecutively enrolled and mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…A key finding was that using the app for weekly screening for PE increased worries about PE, which were magnified if the test-strip colour was perceived as changing. This is consistent with previous studies suggesting that screening can lead to anxiety 27–29. Our findings indicated that the women perceived PE as a threat to themselves and their unborn child even though they were unsure about how to define PE further.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A key finding was that using the app for weekly screening for PE increased worries about PE, which were magnified if the test-strip colour was perceived as changing. This is consistent with previous studies suggesting that screening can lead to anxiety 27–29. Our findings indicated that the women perceived PE as a threat to themselves and their unborn child even though they were unsure about how to define PE further.…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with previous studies suggesting that screening can lead to anxiety. [27][28][29] Our findings indicated that the women perceived PE as a threat to themselves and their unborn child even though they were unsure about how to define PE further. This is consistent with both earlier and more recent studies, finding that women typically have inadequate knowledge of PE.…”
Section: Discussionmentioning
confidence: 69%
“…In breast cancer screening, more negative psychosocial consequences were noted in women who received FP results, with one study reporting persistent psychosocial consequences 12 to 14years after screening in women with FP mammograms [ 10 , 24 ]. In colorectal cancer screening programs, one Danish study reported short-term and long-term psychosocial consequences of receiving a FP or diagnosis of polyps compared to a negative screening result using a condition-specific questionnaire [ 25 ]. There was no evidence of negative impacts from invitation to a colorectal cancer screening program [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only seven articles (21.2%) across three author groups discussed the limitations of the PROMs they used. [42][43][44][45][46]59 However, this reporting was generally deficient and did not focus on the implications for results.…”
Section: Additional Findingsmentioning
confidence: 99%